Spectrum Optimization for Cognitive Satellite Communications With Cournot Game Model - Li Wang; Feng Li; Xin Liu; Kwok-Yan Lam; Zhenyu Na; Hong Peng (IEEE Access, 2018)
With the availability of high-throughput satellite services at affordable cost, terrestrial network providers make use of satellite links to extend their coverage to areas, where land-based communication infrastructures are prohibitively costly to implement. Due to the ever-increasing demand for bandwidth resulted from the rapid development of data-intensive services in recent years, one of the fundamental challenges for satellite communications is to continuously improve utilization efficiency of the scarce satellite spectrum. Cognitive satellite communications address the problem by providing mechanisms for terrestrial and satellite users to dynamically access idle bands of licensed satellite networks, hence enabling spectrum sharing between two satellite systems or between satellite and terrestrial systems. In this paper, we investigate a distributed technique of spectrum sharing for cognitive satellite networks. In order to cater for situations with incomplete decision information, the proposed scheme is based on the Bayesian equilibrium theory. We first develop a spectrum allocation scheme by studying the action strategy of terrestrial cognitive terminals in a distributed competition. A feasible spectrum allocation scheme that caters for cases of incomplete user information is then developed as an extension of the basic scheme by formulating the problem as a Cournot game model. By identifying the unique equilibrium in this model, optimal spectrum allocation for cognitive satellite networks can be achieved. Essential discussions and proofs for the rationality of this method and uniqueness of the equilibrium are provided. Numerical results are given to justify the claimed advantages.